Porous titanium and Ti-35Nb alloy: effects on gene expression of osteoblastic cells derived from human alveolar bone - Prado, Renata Falchete do [UNESP]; Rabelo, Sylvia Bicalho [UNESP]; Andrade, Dennia Perez de [UNESP]; Nascimento, Rodrigo Dias [UNESP]; Rodrigues Henriques, Vinicius Andre; Carvalho, Yasmin Rodarte [UNESP]; Alves Cairo, Carlos Alberto; Reis de Vasconcellos, Luana Marotta [UNESP] (Springer, 2015)
Tests on titanium alloys that possess low elastic modulus, corrosion resistance and minimal potential toxicity are ongoing. This study aimed to evaluate the behavior of human osteoblastic cells cultured on dense and porous Titanium (Ti) samples comparing to dense and porous Ti-35 Niobium (Ti-35Nb) samples, using gene expression analysis. Scanning electronic microscopy confirmed surface porosity and pore interconnectivity and X-ray diffraction showed titanium beta-phase stabilization in Ti-35Nb alloy. There were no differences in expression of transforming growth factor-beta, integrin-beta 1, alkaline phosphatase, osteopontin, macrophage colony stimulating factor, prostaglandin E synthase, and apolipoprotein E regarding the type of alloy, porosity and experimental period. The experimental period was a significant factor for the markers: bone sialoprotein II and interleukin 6, with expression increasing over time. Porosity diminished Runt-related transcription factor-2 (Runx-2) expression. Cells adhering to the Ti-35Nb alloy showed statistically similar expression to those adhering to commercially pure Ti grade II, for all the markers tested. In conclusion, the molecular mechanisms of interaction between human osteoblasts and the Ti-35Nb alloy follow the principal routes of osseointegration of commercially pure Ti grade II. Porosity impaired the route of transcription factor Runx-2.